Alveolar but not intravenous S-ketamine inhibits alveolar sodium transport and lung fluid clearance in rats - Berger, Marc Moritz; Pitzer, Bernhard; Zügel, Stefanie; Wieland, Catharina W.; Vlaar, Alexander P.; Schultz, Marcus J.; Dahan, Albert; Bärtsch, Peter; Hollmann, Markus W.; Mairbäurl, Heimo (Anesthesia & analgesia, 2010)
S-ketamine is frequently used for analgosedation, especially during sepsis and cardiovascular instability. Because S-ketamine blocks voltage-gated sodium (Na+) channels in neurons and skeletal muscle, it is conceivable that S-ketamine also blocks alveolar epithelial Na+ channels that are crucial for alveolar fluid clearance (AFC). We studied the effects of alveolar and IV S-ketamine on transalveolar Na+ transport and AFC, and investigated whether IV S-ketamine enters the alveolar space in response to endotoxemia-induced pulmonary inflammation.
Gesehen am 18.01.2023